MANURE IN SERBIA – QUANTITIES AND GREENHOUSE GAS EMISSIONS - Višković, Miodrag; Djatkov, Djordje; Nesterovic, Aleksandar; Martinov, Milan; Cvetkovic, Slobodan (Journal of Agricultural Sciences (Belgrade), 2022)
Manure is a by-product at agricultural farms that can consist of excrement, bedding, food, and other substances. Manure is a significant form of organic fertilizer, but it generates negative impacts on the environment. The objectives of the manuscript are to determine the quantities of manure and allocate it depending on the size and type of farms in Serbia and to quantify greenhouse gas emissions in Serbia originating from manure management. About 8.6 million m3 of liquid manure and about 9.6 million tons of solid manure are generated in Serbia. The dominant types of manure are liquid pig manure and cattle solid manure. Approximately 72% of the total amount of manure is located at micro-farms with less than 100 CU. At large farms with over 1,000 CU, about 19% of the total amount of manure in Serbia is generated. In 2020, about 23 Gg of CH4 and 1 Gg of N2O were emitted directly from manure. About 1,1 Gg of N2O is emitted indirectly from manure management. Total emissions of greenhouse gases originating from manure in 2020 were about 1,144 GgCO2eq. Greenhouse gas emissions are declining due to the reduction of livestock, so in comparison to 1990, for this sector, they are reduced by 36%.